استغلال نتائج تقييم أداء الموارد البشرية في تحقيق أهداف المؤسسة الرياضية - دحية, خالد (Sciences de l'Homme et de la Société, 2016)
يهدف الباحث من خلال دراسته هذه إلى محاولة التعرف على أهمية استغلال نتائج تقييم  الأداء في المؤسسات الرياضية وتبيين العلاقة بين التصميم والتسيير الجيد لنظام تقييم الأداء وتأثيرها على نتائج التقييم وبالتالي أهداف المؤسسة الرياضية ككل. وأيضا معرفة مختلف الطرق والمعايير المستخدمة في التقييم واستغلال نتائجه للوصول إلى مستوى الأداء المطلوب، وكذا توضيح فائدة التطبيق الفعلي  في الواقع  وما هو مسطر بشكل نظري من طرف -المسؤولين عن الموارد البشرية- كأهداف تسييرية مستمدة من مختلف نظريات التسيير، ومن ثمّ  إظهار القيمة الحقيقية لعملية تقييم الأداء ودورها في تنمية الموارد البشرية وبالتالي تحقيق الأهداف المرغوبة.     Abstract :           The objective of this research is to know the importance from considering  the results of performance evaluation of the human resources in the sports institutions, and showing the nature of the relation between planning and good managing to the organization of  human evaluation and its influence on the results of evaluation and the objectives of the establishment. Moreover knowing the various ways and standards used for evaluating and exploiting that results to reach the expected level in performance.In addition illustrating the benefit from the real application of that idea and what is given as theoretical papers from responsibles as objectives, which are taken from different management theories, therefore showing the real value from the performance evaluation and its role in developing human resources and realizing the Wishes objectives.